GEJOLAK INDO-PASIFIK: ANALISIS KEBIJAKAN AUSTRALIA DALAM MERESPON ANCAMAN TIONGKOK DI KAWASAN INDO-PASIFIK - Arfa Bahrul Ulum; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Australia conducts defense cooperation with Japan within the framework of the Reciprocal Access Agreement (RAA). The signing of this cooperation was carried out online on January 6, 2022. The signing of this defense cooperation is the second in a period of 6 months after previously Australia did it with the United States and Britain. Meanwhile in the Indo-Pacific, China continues to exert influence in the region and carries out several threatening activities. This research will try to explain the phenomenon between Australia and Japan and its relationship with China. This research will use the formulation of the problem